- #1

wei1006

- 6

- 0

Simplify 2sec^2x-2sec^2xsin^2x-sin^2x-cos^2x

2)Relevant equations:

tan A=sinA/cos A

1+tan^2A=sec^A

cot A=1/tanA

cot A=cos A/sinA

sin^2A+cos^2A=1

secA=1/cos A

cosecA=1/sinA

1+cosec^2A= cot^2A

sin2A=2sinAcosA

cos2A=1-2sin^2A=cos^2A-sin^2A=2cos^A-1

tan2A=(2tanA)/1-tan^2A

3) Attempt:

2sec^2x-2sec^2xsin^2x-sin^2x-cos^2x

= 2sec^2x(1-sin^2x)-sin^2x-cos^2x

= 2sec^2x(cos^2x)-sin^2x-cos^2x

I am stuck after this... Will be helpful if some clues are provided. Thank you!